Epistemología de virtudes robusta: sobre los límites y las posibilidades de su aplicación a la prueba de los hechos en el derecho - Pedro H. Haddad Bernat (Crítica)
The purpose of this paper is to define the general features of a suitable epistemology for law. In particular, the paper is concerned with a very influential project that is nowadays offered in the literature: robust virtue epistemology. As I will show here, such a project is untenable for law, since a satisfactory and complete epistemology of legal proof requires the conjunction of both the agent’s perspective (the “trier-of-facts”) and the inquiry system’s perspective (the rules of evidence). Keywords: legal epistemology, judicial reasoning, legal fact-finding, epistemic virtues, virtue jurisprudence